Acute kidney injury and hypercalcemia associated with veterinary supplements applications in adult man - Frutuoso Bezerra, Rádames; de Souza Andrade, Tacilla Hanny; Bezerra de Araújo, Flávio; Lima, Rafael Siqueira (Journal of Health & Biological Sciences, 2024)
The compound “ADE” is an injectable oil for veterinary use which contains large amounts of vitamins A, D and E. The parenteral application in humans leads to a granuloma reaction which triggers hypercalcemia. A 42-year-old man was admitted with lower limb pain, nephrolithiasis and nephrocalcinosis. Laboratory tests revealed creatinine 4.59 mg/dl, calcium 13.3 mg/dl and parathormone 13.8 pg/ml. He underwent an ureterolithotripsy, stent placement, intravenous crystalloid fluids, and corticosteroid. He improved symptoms, kidney function and normalized serum calcium. The “ADE”-induced hypercalcemia diagnosis can be challenging. The early diagnosis may avoid negative outcomes.